Taking advantage of lithium monohalocarbenoid intrinsic α-elimination in 2-MeTHF: controlled epoxide ring-opening en route to halohydrins. Issue 9 (18th February 2021) - Ielo, Laura; Miele, Margherita; Pillari, Veronica; Senatore, Raffaele; Mirabile, Salvatore; Gitto, Rosaria; Holzer, Wolfgang; Alcántara, Andrés R.; Pace, Vittorio
Abstract : Lithium monohalocarbenoids are useful synthons for conducting C1-homologations, although their high tendency to undergo degradative α-elimination, leading to a lithium halide and a free carbene, is the main drawback for expanding their use in synthesis. Abstract : The intrinsic degradative α-elimination of Li carbenoids somehow complicates their use in synthesis as C1-synthons. Nevertheless, we herein report how boosting such an α-elimination is a straightforward strategy for accomplishing controlled ring-opening of epoxides to furnish the corresponding β-halohydrins. Crucial for the development of the method is the use of the eco-friendly solvent 2-MeTHF, which forces the degradation of the incipient monohalolithium, due to the very limited stabilizing effect of this solvent on the chemical integrity of the carbenoid. With this approach, high yields of the targeted compounds are consistently obtained under very high regiocontrol and, despite the basic nature of the reagents, no racemization of enantiopure materials is observed.